2018
DOI: 10.1038/s41467-017-02113-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer-associated long non-coding RNA LEENE regulates endothelial nitric oxide synthase and endothelial function

Abstract: The optimal expression of endothelial nitric oxide synthase (eNOS), the hallmark of endothelial homeostasis, is vital to vascular function. Dynamically regulated by various stimuli, eNOS expression is modulated at transcriptional, post-transcriptional, and post-translational levels. However, epigenetic modulations of eNOS, particularly through long non-coding RNAs (lncRNAs) and chromatin remodeling, remain to be explored. Here we identify an enhancer-associated lncRNA that enhances eNOS expression (LEENE). Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 65 publications
5
114
0
1
Order By: Relevance
“…The delivery of the CRISPR/Cas9 components into primary endothelial and other hard-to-transfect cells has been a major obstacle for cardiovascular research. Plasmids, lenti-, adeno-or adeno-associated viral vectors have most often been used to achieve sufficient gene knockout rates in ECs (Abrahimi et al, 2015;Cullere, Plovie, Bennett, MacRae, & Mayadas, 2015;Gong et al, 2017;Miao et al, 2018;Wu et al, 2017). Just recently, we have demonstrated that gene knockouts in human ECs can be established with a crR-NA:tracrRNA:Cas9 RNP approach (Schwefel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The delivery of the CRISPR/Cas9 components into primary endothelial and other hard-to-transfect cells has been a major obstacle for cardiovascular research. Plasmids, lenti-, adeno-or adeno-associated viral vectors have most often been used to achieve sufficient gene knockout rates in ECs (Abrahimi et al, 2015;Cullere, Plovie, Bennett, MacRae, & Mayadas, 2015;Gong et al, 2017;Miao et al, 2018;Wu et al, 2017). Just recently, we have demonstrated that gene knockouts in human ECs can be established with a crR-NA:tracrRNA:Cas9 RNP approach (Schwefel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies demonstrate that the latest human genetics approaches such as caQTL mapping (23), allelic imbalance assay (24), and CRISPR-based assays (20,21) are powerful tools to investigate possible genetic contributions to cellular mechanotransduction. Miao et al recently applied CRISPR-Cas9 to achieve high efficiency of a 10 kb deletion of an enhancer region in bulk HUVEC (40). In this study we expanded the applications of CRISPR-based techniques to investigate key vascular functions.…”
Section: Discussionmentioning
confidence: 99%
“…ChIP assays were performed as previously described (Miao et al, 2018). Briefly, 1×10 7 human fetal endocardial cells or iPSC-ECs were treated with 0.75% formaldehyde for 20 minutes at room temperature.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%